IMPORTANCE OF MANDIBULAR THIRD MOLAR IMPACTIONS IN ORTHODONTIC TREATMENT - Muhammad Azeem; Muhammad Mudassar Saleem; Syeda Rabbab Hasan; Bushra Naeem Khan; Muhammad Jamal; Saadia Ata (Pakistan Oral & Dental Journal, 2020)
The aim of the present study was to find out the pattern of impacted mandibular third molars in orthodontic patients. Present retrospective cross-sectional study was carried out at orthodontics department of de’Montmorency College of Dentistry, Lahore and Dental Section, Faisalabad Medical University, Faisalabad, from January 2016 to January 2019. Total 125 orthopantomograms (OPGs) of 20-40 years old patients were evaluated in the present study. The pattern of impacted mandibular third molars was recorded in terms of their angulation to the long axis of second molars. Wintersâ€™ classification was used to classify the impacted lower third molars into 4 types: Mesioangular, horizontal, distoangular and vertical. Results showed that the most common type of impacted mandibular third molar was mesioangular followed by horizontal, distoangular and vertical. It was concluded that present study will also help in understanding the pattern of impacted third molar globally. There were certain limitations of the present study such as decreased sample size, hospital based sampling, lack of randomization, and retrospective nature. It was concluded that by finding the angulation of third molars, orthodontists can plan extractions, final occlusal relations and retention therapy more efficiently. The early extraction of mesioangular impactions can prevent second molar distal caries, which in turn will benefit the dental health of an orthodontic paitent.